Acute Pancreatic Infarction Caused by Malignant Hypertension: a Case Report - Yun BAI, Dingxin WANG, Yanzhao SUN, Jimin ZHENG, Jian ZHANG, Yuzhen WANG, Gaifang LIU (Zhongguo quanke yixue, 2022)
Malignant hypertension is a common hypertensive emergency, which generally progresses rapidly, often affects important target organs such as the heart, brain, and kidney, leading to organ insufficiency. Malignant hypertension may develop serious complications, among which thrombotic microangiopathy is mainly characterized by impaired tissue and organ functions due to thrombosis in the microcirculation, with critical condition and poor prognosis generally. Pancreatic involvement in malignant hypertension is rare, whose prognosis may be extreme poor and mortality may be high due to insufficient understanding of it, and lack of clinical evidence on its early diagnosis and treatment. We reported the diagnosis and treatment of a case of acute pancreatic infarction caused by malignant hypertension, aiming at providing a reference for clinical practice.